ANALISIS DAN DESAIN SISTEM PRODUKSI SERAT PUTIH MENGGUNAKAN LIMBAH PADAT SABUT KELAPA SAWIT (PALM PRESS FIBRE): Analysis and Design of White Fiber Production System Using Palm Oil Solid Waste (Palm Press Fiber) - Wilda Harlia Devita; Rafika Ratik Srimurni (Universitas Darussalam Gontor, 2022)
An effort to assist management in planning and making decisions regarding the optimal allocation require design and system analysis and formulation. Based on these conditions, it is necessary to analyze and plan a white fiber production system using solid waste of palm press fibre. The purpose of this paper is to create a design and system for producing white fiber using solid waste of palm oil (palm press fiber) and optimizing the productivity of white fiber by minimizing costs. The method used in making designs and systems is by developing systems, namely system analysis, system design, system implementation using the sybase power designer software and the optimal solution determination technique used is the simplex method processed using WinQSB software. The results of the system design are implemented successfully and the results of the model logic verification are correct. In the formulation of cost minimization has been obtained minimizing production costs by immersing 90 minutes for optimal productivity. Therefore, the results of the analysis that has been carried out to maximize the income of the production company, the production process is carried out for 630 minutes at a production cost of IDR 59,610,000 with a production capacity of 1000 kg.